Green Banking in Albania: Examining Its Impact on Environmental Performance, Financing, and Corporate Image - FEIMI, Dorjana; VELA, Fioralba (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025DO - 10.14505/tpref.v16.1(33).17, 2025)
In recent years, the banking sector has increasingly embraced eco-friendly practices to address environmental, social, and governance (ESG) challenges while promoting environmental preservation. In Albania, banks have begun implementing green banking strategies; however, limited empirical research exists on the measurement and impact of these initiatives. This study examines the effects of green banking practices on environmental sustainability, green financing, and the green image of banks in Albania. Data were gathered through self-administered and online surveys targeting employees in the Albanian banking sector, and regression analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The findings indicate a significant positive relationship between green banking practices and improvements in environmental sustainability, green financing activities, and the overall corporate image of banks. The results underscore the importance of adopting green banking practices to enhance sustainability efforts, expand green financing opportunities, and strengthen banks' reputations. The study recommends that banks prioritize environmental education and training for employees, introduce incentive programs for green initiatives, and integrate sustainable practices into daily operations, such as reducing paper consumption, utilizing energy-efficient technologies like Smart BanKomaT (ATM), and expanding online banking platforms. Additionally, the Bank of Albania and the government should establish targeted regulations and facilitate awareness-raising events, such as seminars and training sessions, to engage customers and the public in green banking initiatives. These actions are expected to enhance environmental sustainability while supporting Albania’s sustainable economic growth.